A NOTE ON PODOCONIS MEGASPERMA BOEDIJN - MIEN A. RIFAI (Research Center for Biology, 1975)
The lectotype specimen of Podoeonis megasperma is selected and this species is reclassified as Exosporium megaspermum (Boedijn) Rifai, a newly proposed combination.An illustrated redescription is presented.